Project maturity evaluation model for SMEs from the software development sub-sector (2016)
The purpose of the paper is to present a project management maturity model for SMEs oriented to software development. The proposal is based on CMMI capability maturity model, and the SCAMPI evaluation method. The proposal includes a quantitative satisfaction scale, redundant evidence assessment, and multiple criteria for selecting experts. The proposal was validated with a case study carried out in a medium-sized company from the Information and Communications Technology sector. The model concluded that the company did not reach maturity level 2; however it showed that 92% of the processes from maturity level 2 and 77% of the total process had already been implemented, which allows the company to adopt a specific orientation for its improvement efforts.